Access, Skills and Constraints of Barangay Officials towards the Use of Information and Communications Technology (ICT) - Jr, Cereneo S Santiago; Ulanday, Ma Leah P.; Centeno, Zarah Jane R.; Bayla, Ma. Cristina D. (International Journal of Knowledge Content Development & Technology, 2021)
ABSTRACT - The study determined the access, skills and constraints towards the usage of ICT among barangay officials. A complete enumeration technique was used due to the small size of the population. A total of 121 barangay secretaries and barangay treasurers comprised the study respondents. The findings revealed that most of barangay officials have access to personal computer at home and in the office using their own mobile data and office internet connectivity. With the support from the Local Government Unit (LGU), it was found that most of the respondents are advance and proficient in computer usage. As constraints to ICT usage, the study respondents still experienced slow internet bandwidth that makes connection and communication weak along with the low income status. Consequently, it was found that there are no significant differences in terms of skills and constraints among barangay secretaries and barangay treasurers towards using ICT. It can be concluded that study respondents prefer to use office computer to access the information they need due to the convenience and availability of resources. The study respondents are competent enough to handle their job well but listed slow internet and low financial resources may hamper their ICT usage. Research implications are also offered. URL: http://ijkcdt.net/xml/29429/29429.pdf